(3HdHd GdCaQGM hQGMI GdCQhGM hePgH GdCJQGM hfSejGJ GdSMQ hfaMGJ GdRgQs - (3CHh YHO Gddg eMeO Hf Ydj Hf CMeO Hf EHQGgje Hf eMeO GdShOi GdTgjQ HGdgGOis; (3GdShOj (B- (3GdgGOj Gdjefj , eMeO Hf Ydj Hf eMeO GdShOj, CHh YHO Gddg eMjj GdOjf GdgGOj Gdjefj,J (B932 (3g` s ((3eMeO Hf eMeO bGjO MSf s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe CgdkG hSgdkG Hce jG LjQI GdMdd heQMHkG HMOGI GdYjS hGdcdd s
(3BNQgG (B:s
(3fhQ GdefGRd ai GdbdH fGRd Je OjhGf SjOi s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3fXes
Keywords: (3GdCOHs